2014
DOI: 10.3855/jidc.4974
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia is associated with disease severity in patients with dengue

Abstract: Introduction: Dengue hemorrhagic fever (DHF) is a major cause of morbidity and mortality in tropical regions. Serum free calcium (Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…We observed a decrease in albumin, along with elevated alanine transaminase (ALT) and aspartate transaminase (AST) in both PI and SI (Table 4) denoting liver inflammation, which has been associated with severity (Oliveira et al 2016, Posadas-Mondragón et al 2017; however, there were no cases of acute hepatitis marked by >10 times ALT increase, unlike in other studies (Souza et al 2004). It has been reported that Ca 2+ levels correlate with disease severity, with hypocalcemia being more prevalent in DHF than in DF (Constantine et al 2014). Our results agree with that report, although hypocalcemia was found at a similar percentage in PI and SI (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…We observed a decrease in albumin, along with elevated alanine transaminase (ALT) and aspartate transaminase (AST) in both PI and SI (Table 4) denoting liver inflammation, which has been associated with severity (Oliveira et al 2016, Posadas-Mondragón et al 2017; however, there were no cases of acute hepatitis marked by >10 times ALT increase, unlike in other studies (Souza et al 2004). It has been reported that Ca 2+ levels correlate with disease severity, with hypocalcemia being more prevalent in DHF than in DF (Constantine et al 2014). Our results agree with that report, although hypocalcemia was found at a similar percentage in PI and SI (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…Unlike serum total calcium, serum ionized calcium (SIC) is not affected by other factors. A recent study revealed that SIC levels were significantly lower and hypocalcaemia was more prevalent in patients with dengue haemorrhagic fever (DHF) than in patients with DF [2]. …”
mentioning
confidence: 99%
“…Ultrasound Scan provides a quick assessment of TSFA. In previous studies TSFA was not objectively measured and ionized calcium levels were not serially done during hospital stay [1,2].…”
mentioning
confidence: 99%
“…However, no real correlation was seen with severity of dengue and reduction in LVEF occurring in all stages of clinical severity. Constantine et al [47] described echocardiographic features of myocarditis in 8 out of 37 adult and pediatric patients with dengue, and all of these patients belonged to the category of DHF. Reduced LVEF below 60% was noted only in four patients.…”
Section: Echocardiography and Cardiac Imagingmentioning
confidence: 99%